2022
DOI: 10.1371/journal.pone.0268960
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally friendly, but behaviorally complex? A systematic review of e-scooter riders’ psychosocial risk features

Abstract: Introduction E-scooters have made a place for themselves on urban roads as an affordable, easy-to-use and environmentally friendly method of transportation. However, and partly because of their road behaviors and safety outcomes, e-scooter users have started to represent a focus of attention for transport planners and policymakers. Aim The present systematic review aims to target and analyze the existing studies investigating the psychosocial characteristics of e-scooter riders, focusing on their behavioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Fear of contagion has kept people away from public transport and car sharing, causing a massive use of private vehicles for travel in various contexts. This is why several national governments and public administrations have focused on enhancing alternative and sustainable means of transport for a new mobility (Useche, Gonzalez-Marin, Faus, & Alonso, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Fear of contagion has kept people away from public transport and car sharing, causing a massive use of private vehicles for travel in various contexts. This is why several national governments and public administrations have focused on enhancing alternative and sustainable means of transport for a new mobility (Useche, Gonzalez-Marin, Faus, & Alonso, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers from other countries have investigated behaviours and attitudes of e-scooter riders and uncovered: a concern over a lack of clear legislation; a difference in safety perception between riders and non-riders; and a generally negative perception of e-scooter riders. A systematic review on psychosocial risky behaviours of e-scooters by Useche et al ( 15 ) found that e-scooters were mostly used by young, highly educated, urban-dwelling males, usually for short trips. They highlighted that groups with low risk perception were more susceptible to undertake risky behaviours, contributing to a higher risk of being involved in a collision.…”
Section: Introductionmentioning
confidence: 99%